Kinerja Keuangan, Tipe Industri dan Sustaiability Report - Arisandi, Cika; Mimba, Ni Putu Sri Harta (E-Jurnal Akuntansi; Vol 31 No 11 (2021)DO - 10.24843/EJA.2021.v31.i11.p05, 2021)
The number of issues of environmental damage due to company activities makes the sustainability report important to disclose. Disclosure of sustainability reports can explain how the company manages the social and environmental problems it causes. The purpose of this study was to determine the effect of financial performance, which is proxied by profitability, liquidity, and leverage as well as the effect of industry type on the disclosure of the sustainability report. This research was conducted on companies that won the Asia Sustainability Reporting Rating in 2017-2019. The sample in this study amounted to 16 companies, using purposive sampling technique. The analytical method used is multiple linear analysis. From the results of the analysis, it is found that profitability, liquidity, and type of industry have a significant effect on the disclosure of the sustainability report. Meanwhile, leverage has no significant effect on the disclosure of the sustainability report. Keywords: Profitability; Liquidity; Leverage; Industry Type; ASRRAT.